Anti-Corruption Consensus as a Prerequisite for Indonesia’s Progress: An Analysis of the Roles of Government, Religious Leaders, and Society - Hasan Syahrizal; Nur Hana Azizah (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2026)
Corruption as a systemic phenomenon has become a major obstacle to Indonesia’s progress, as it involves government, religious leaders, and society in practices that undermine social integrity. This study aims to analyze the roles of government, religious leaders, and society in building an anti-corruption consensus as a prerequisite for Indonesia’s progress. This research employs a qualitative approach with a descriptive-analytical design through library research based on scholarly sources and credible institutional reports. The findings reveal that corruption in Indonesia is multidimensional and institutionalized within social structures, reinforced by weak governance integrity, moral compromises among religious leaders, and a permissive societal culture toward corrupt practices. Furthermore, anti-corruption efforts that lack cross-sectoral synergy tend to be ineffective and unsustainable. Therefore, an anti-corruption consensus based on collective commitment among government, religious leaders, and society emerges as a strategic solution to foster a culture of integrity. The implications of this study emphasize the importance of strengthening ethical values, institutional reform, and active public participation as fundamental pillars for achieving a just and progressive Indonesia